STRATEGI KETERIKATAN PELANGGAN DI MEDIA SOSIAL UNTUK OPTIMALISASI KEGIATAN UMKM DI ERA DIGITAL - Dwi Martiyanti; Murwani Eko Astuti; Alexander Barus; Anggono Anggono; Edison Parulian (Jurnal Pengabdian Kepada Masyarakat Digital, 2023)
The use of social media by the public in Indonesia to interact and communicate with individuals and products has increased. Business actors can use social media to support business activities in strengthening competitiveness and expanding their market. However, in reality, still many business actors have not maximized the consistent use of social media and even lack knowledge in utilizing this technology. This method of community service was applied in lectures and interactive dialogues/discussions through webinars. The activity results show an increasing public understanding of digital media use, especially social media, to support their business. Participants understood strategies concerning customer engagement when using social media as a marketing tools. It is recommended that counseling and training technically related to digital media as business support are regularly conducted so that MSMEs can increase their productivity and competitiveness.Kata Kunci: digital marketing, social media, engagement strategy, MSMEs